Impact of Cooking Duration on Calcium Oxalate Needle-like Crystals in Plants: A Case Study of Vegetable Taro Flowers in Yunnan - Haoyu Zi; Rui Chen; Nan Jia; Yuxuan Ma; Chunchang Zhao; Zhe Chen; Jingwei Zhang (Foods)
As a popular vegetable in Yunnan Province, China, taro flowers are delicious but contain substances that can cause numbing and mucous membrane damage. Prolonged high-temperature cooking is used by locals to mitigate these effects, though its mechanisms were previously unexplored. This study confirms the presence of needle-like calcium oxalate crystals in taro flowers and shows that prolonged steaming reduces their quantity, size, and sharpness, making them safer to eat. Microscopic observations revealed numerous sharp-tipped (~50 μm) calcium oxalate crystals in fresh taro flowers. After 2 h of steam heating, there were significantly fewer (~80% reduction) and smaller crystals (~70% reduction). Ion chromatography showed no significant change (p > 0.05) in calcium oxalate content (remaining ~2.5% of dry weight) after heating. Higher temperatures increase calcium oxalate solubility, causing gradual dissolution and the likely formation of small irregular structures, thus reducing the numbing effect. Prolonged cooking could be applied to other plant-based foods and medicines rich in these crystals. By analyzing statistics related to taro and taro flowers, the estimated potential economic benefits of commercializing taro flowers were USD 2.58–12.92 billion annually, potentially improving food security, creating jobs, and promoting development across regions where taro is largely cultivated in the Global South.